THE JOURNEYS OF 'ABD AL-GHANĪ AL-NĀBULUSĪ IN PALESTINE (1101/1690 AND 1105/1693) - Sirriyyah, Elizabeth (Journal of Semitic studies, 1979)
ELIZABETH SIRRIYYAH; THE JOURNEYS OF 'ABD AL-GHANĪ AL-NĀBULUSĪ IN PALESTINE (1101/1690 AND 1105/1693), Journal of Semitic Studies, Volume 24, Issue 1, 1 March 1